2007
DOI: 10.1111/j.1745-7254.2007.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of hepatitis B X-interacting protein (HBXIP) in proliferation regulation of cells

Abstract: Aim: To investigat the effect of Hepatitis B X-interacting protein (HBXIP) on cell proliferation. Methods: A rabbit antibody against HBXIP was generated. The RNA interference (RNAi) fragment of the HBXIP gene was constructed in the pSilencer-3.0-H1 vector termed pSilencer-hbxip. Plasmids of the pcDNA3-hbxip encoding HBXIP gene and pSilencer-hbxip were transfected into human breast carcinoma MCF-7 cells, hepatoma H7402 cells, and the normal human hepatic cell line L-O2, respectively. 3-[4,5-dimethylthiazol-2-yl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…We previously demonstrated that HBXIP was a novel important oncoprotein in the development of cancer. HBXIP was overexpressed in clinical breast cancer tissues and could promote proliferation and migration through NF-B, MAPK/ERK, or PI3K/AKT pathways in breast cancer cells (6,7). Recently, we have discovered that HBXIP acts as a novel oncogenic coactivator of transcription factors, such as STAT4, SP1, E2F1, and TFIID to transactivate S100A4, LMO4, Skp2, and Lin28B in promotion of growth and migration of breast cancer cells (8 -11).…”
Section: Hepatitis B X-interacting Protein (Hbxip)mentioning
confidence: 99%
“…We previously demonstrated that HBXIP was a novel important oncoprotein in the development of cancer. HBXIP was overexpressed in clinical breast cancer tissues and could promote proliferation and migration through NF-B, MAPK/ERK, or PI3K/AKT pathways in breast cancer cells (6,7). Recently, we have discovered that HBXIP acts as a novel oncogenic coactivator of transcription factors, such as STAT4, SP1, E2F1, and TFIID to transactivate S100A4, LMO4, Skp2, and Lin28B in promotion of growth and migration of breast cancer cells (8 -11).…”
Section: Hepatitis B X-interacting Protein (Hbxip)mentioning
confidence: 99%
“…The stained cells were passed through a nylon-mesh sieve to remove cell clumps and were then analyzed by a FACScan flow cytometer (Becton Dickinson, San Jose, CA, USA); the results were analyzed using CellQuest software (Becton Dickinson). The cell PI was calculated as the sum of the S and G2/ M phase cells, expressed as a fraction of the total cell population (PI=((S+G2/M)/(G0/G1+S+G2/M))×100) [53]. The flow cytometry experiment was repeated three times.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…The data showed that L-O2-X cells grew faster than controls. The proliferation index (PI) is the sum of the S and G 2 /M phase activities of the cell cycle expressed as a fraction of the total cell population, that is PI=[(S+G 2 /M)/(G 0 / G 1 +S+G 2 /M)] ×100% [30] . A high PI value corresponds with fast cell proliferation.…”
Section: L-o2-x Cells Grow Faster Than Controlsmentioning
confidence: 99%
“…The following luciferase reporters were used: pGL3-Survivin, pGL3-NF-κB, pGL3-hTERT, and pGL3-AP-1, pGL3-basic, pGL3-control and the Renilla Luciferase Reporter Vector pRL-TK vector. Cells were harvested after 48 h and lysed in 1×passive lysis buffer according to the manufacturer's protocol [30] . The luciferase activity was determined and normalized to a cotransfected control reporter by using the Dual-Luciferase Reporter® Assay System (Promega, USA) on a Luminometer (TD-20/20, Turner Desings) according to the manufacturer's instructions.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%